Effect of religiosity, perceived risk, and attitude on tax compliant intention moderated by e-filing - Mekar Satria Utama; Umar Nimran; Kadarisman Hidayat; Arik Prasetya (International Journal of Financial Studies, 2022)
This research examined the effect of Religiosity, Perceived Risk, and Attitude on Tax Compliant Intention, moderated by e-Filing. This research used a quantitative approach which involved the Structural Equation Model (SEM). Large taxpayers are generally in the form of agencies and individuals, so the population of this study comprised of companies that are in the Directorate General of Taxation of Large Taxpayers Jakarta, Large Tax Service Offices 1 and 2, totaling 529 companies. Religiosity (X1) and Perceived Risk (X2) significantly influence Attitude (Y1). Furthermore, Attitude (Y1) has a positive and significant effect on Tax Compliant Intention (Y2). e-Filing showed an insignificant moderating effect on the research model. The novelties are the development of the Theory of Planned Behavior by involving other variables that affect taxpayer compliance behavior, namely Religiosity and the perceived risk of taxpayers. In addition, this research involves the e-Filing variable as a moderating variable.
Keywords: G32; H23; Z12; 330; attitude; e-Filing; perceived risk; religiosity; tax compliant intention